“Cults,” Coercion, and Control: Rhetoric, Reality, and the Return of “Brainwashing”? - Sessions, Erin Martine; Doherty, Bernard (Implicit Religion, 2023)
In the face of what has been called an epidemic of domestic and family violence (DFV) in several countries, scholarly analysts, journalists, and policymakers have increasingly turned to the matrix of ideas around what Evan Stark has called coercive control, for insights into the dynamics of abusive relationships. In seeking to address this social problem, some commentators—in both the DFV research space and cultic studies— have begun to see a link between New Religions (“cults”) and coercive control, and use the language of coercive control to revive a problematic rhetoric linked to ideas about so-called “brainwashing.” This article highlights some of the commonalities between coercive control, as theorized by Stark and others, and the classic work on coercive persuasion as this was applied—sometimes disingenuously—to a wave of New Religions during the 1970s through to the 1990s. Secondly, this article analyses the rhetorical use of elements of the “cult stereotype” in contemporary popular and academic discussions of DFV and how the language of coercive control has been employed. We conclude that the use of coercive control language in cultic studies is largely superficial and engages in tactical ambiguities which seek to apply various “cultic brainwashing” ideas in a new context and suggest that this approach is unhelpful both to victim-survivors of DFV and those who have experienced abuse in particular New Religions or, indeed, within mainstream religion.